Marx, Critical Theory, and Religion: A Critique of Rational Choice - Goldstein, Warren (Brill Academic Publishers, 2005)
Intro -- Contents -- Acknowledgements -- Introduction: Marx, Critical Theory, and Religion: A Critique of Rational Choice --- Warren S. Goldstein -- Part I: Marx -- Opium as Dialectics of Religion: Metaphor, Expression and Protest --- Andrew M. McKinnon -- The Origin of Political Economy and the Descent of Marx --- William Clare Roberts -- Part II: Critical Theory -- Toward a Dialectical Sociology of Religion: A Critique of Positivism and Clerico-Fascism --- Rudolf J. Siebert -- Psalm 91 --- Max Horkheimer -- The Notion of the Totally "Other" and its Consequence in the Critical Theory of Religion and the Rational Choice Theory of Religion --- Michael R. Ott -- From A Beautiful Mind to the Beautiful Soul: Rational Choice, Religion, and the Critical Theory of Adorno & Horkheimer --- Christopher Craig Brittain -- Intersubjectivity and Religious Language: Toward a Critique of Regressive Trends in Thanatology --- Kenneth G. MacKendrick -- Part III: Religion -- Ancient Judaism and Early Christianity: A Critical Dialectical/Conflict Approach to Biblical History --- Warren S. Goldstein -- The Concept of Choice in the Rise of Christianity: A Critique of Rational-Choice Theory --- George Lundskow -- Speaking in Tongues: A Dialectic of Faith and Practice --- Bonnie Wright and Anne Warfield Rawls -- From the Caliphate to the Shaheedim: Toward a Critical Theory of Islam --- Lauren Langman -- Operationalizing The Critical Theory of Religion --- David Gay,Warren S. Goldstein, and Anna Campbell Buck -- About the Authors -- References -- Index.